Approach to the Patient: Ethics Cases in Pediatric Endocrinology and Their Management - Jennifer M Ladd; Meaghann S Weaver; Rohan K Henry (The Journal of Clinical Endocrinology & Metabolism, 2026)
Abstract Context With advancing technologies and expanding indications for existing therapies, ethical dilemmas increasingly arise in pediatric endocrinology practice. Aim This article presents practical, case-based scenarios to guide clinicians in navigating common ethical challenges in pediatric endocrinology. Cases We present four case vignettes which present ethical dilemmas regarding (1) growth hormone treatment prescribed for idiopathic short stature, (2) precocious puberty management in a child with neurodevelopmental delay, (3) technology use in type 1 diabetes care, and (4) glucagon-like peptide 1 receptor agonist use for obesity management. For each case, we outline patient presentations and management approaches which highlight the application of the four-principle ethical framework based on Beauchamp and Childress. Salient historical events are mentioned to serve as a basis to contextualize and situate the specific ethical dilemmas. Conclusion Ethical dilemmas have the potential to arise in the everyday practice of pediatric endocrinology. Application of the principles of beneficence, non-maleficence, respect for autonomy, and justice will allow for a pragmatic incorporation of ethical decision making in medical care.